2021
DOI: 10.1099/mgen.0.000713
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of β-lactam resistance under ampicillin treatment in gut microbiota suffering from pre-disturbance

Abstract: Ingestion of food- or waterborne antibiotic-resistant bacteria may lead to dissemination of antibiotic resistance genes (ARGs) in the gut microbiota. The gut microbiota often suffers from various disturbances. It is not clear whether and how disturbed microbiota may affect ARG mobility under antibiotic treatments. For proof of concept, in the presence or absence of streptomycin pre-treatment, mice were inoculated orally with a β-lactam-susceptible Salmonella enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…As such, immediately following antibiotic treatment, the gut microbiome may provide a great ecological opportunity for ARB to colonize and disseminate their ARGs, even in the absence of antibiotics [32,33]. Previous studies have demonstrated the conjugative transfer of antibiotic resistance plasmids following heavy-dose streptomycin treatments for clearing the mouse gut [19,20]. Depending on the chemical composition, formulation and administration route, antibiotics may cause different magnitudes of perturbation to the gut microbiome [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, immediately following antibiotic treatment, the gut microbiome may provide a great ecological opportunity for ARB to colonize and disseminate their ARGs, even in the absence of antibiotics [32,33]. Previous studies have demonstrated the conjugative transfer of antibiotic resistance plasmids following heavy-dose streptomycin treatments for clearing the mouse gut [19,20]. Depending on the chemical composition, formulation and administration route, antibiotics may cause different magnitudes of perturbation to the gut microbiome [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, through indirect pre-exposure, heavy antibiotic dosages (e.g. one oral dose of streptomycin at 1 g kg -1 ) can disrupt the gut microbiota, promoting the colonization and expansion of ARB and fostering conjugation [19,20]. However, it remains unclear whether ARB are able to colonize and disseminate their ARGs within the gut microbiome that have been pre-exposed to clinical or veterinary uses of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Under the treatment of antibiotics, the donor bacteria (cells carrying drug-resistant plasmids) and Enterobacteriaceae (the main recipient cell) in the gastrointestinal tract grow in large numbers, thereby promoting plasmid conjugation. For example, the CF of plasmids carrying the bla CMY-2 gene was significantly increased after the intestinal microbiota was exposed to ampicillin, and the gene maintained a relatively high abundance in the intestine for a long time ( Table 1 ) [ 39 ]. Therefore, the selective action of antibiotics against bacteria carrying resistant plasmids and Enterobacteriales is a key factor affecting the density of donor and recipient bacteria and the transmission efficiency of ARGs in the gastrointestinal tract.…”
Section: Factors Influencing Conjugation In Vivomentioning
confidence: 99%
“…The β-lactam class of antibiotics encompasses a broad spectrum of antimicrobials, including ampicillin, penicillin, and cephalosporins, comprising 65% of the world market for antibiotics . To date, β-lactamases have been considered as one of the major mechanisms of resistance in the fight against β-lactam class of antibiotics by acting on the bacterial cell wall synthesis. , This mechanism of resistance is even more common in microorganisms that reside in the human gut and play a protective role in minimizing the damage caused by antibiotics. Conceptualized approaches to β-lactamase administration were shown to impart changes to the gut resistome through antibiotic inactivation. , These studies emphasized the potential of the inactivation of β-lactam antibiotics to protect the gut microbiome in the gastrointestinal tract (GI) tract. However, the role of β-lactamases on various organisms is not fully understood due to the lack of model systems that can facilitate the evaluation of specific organisms’ interaction in a dynamic manner.…”
Section: Introductionmentioning
confidence: 99%